Effects of manual therapy in the treatment of temporomandibular dysfunction - a review of the literature - Castro, Mirjam Evi Braun de; Silva, Rodrigo Marcel Valentim da; Basilio, Franciane Batista (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: The term temporomandibular dysfunction (TMD) applies to functional changes related to temporomandibular joint (TMJ) and it is associated to masticatory structures. The main symptoms are pain in the TMJ region and / or the masticatory musculature. Objective: to perform a systematic review on the effects of manual therapy in the treatment of TMD. Methods: We analyzed 231 articles from the databases of Bireme, BVS, Lilacs, MedLine, PEDro, Pubmed and, Scielo. Of these, only 30 were selected for the elaboration of the article and 6 were used for the qualitative synthesis. Studies of controlled clinical trials of high methodological quality and high clinical relevance on the PEDro scale were included, which used the same evaluation measures, VAS (visual analogic scale), PPT (pressure pain threshold) and maximum mouth opening (MMO), and only one treatment technique comparing the control group with placebo. Result: The studies presented positive results for pain in VAS, PPT and MMO; however, there are significant differences depending on the technique. Myofascial release has a strong efficacy in reducing the symptoms of acute pain in the long term, but does not show clinically significant changes in mouth opening amplitude and MMO. Mobilization / manipulation presents significant changes in MMO, significantly improving the efficacy of mouth range of motion in the treatment of the short-term pain symptom, however does not sustain in the long term. Conclusion: The tool for the individual treatment of patients is based on the symptoms addressed, significantly improving the effectiveness of the range of motion of the mouth in the treatment of joint mobilization / manipulation, and treatment of pain by myofascial release.